A composite function is commonly written into some other function. It's also accomplished by replacing one function with a second and it has two functions, f, and g, which generate a new function, and the further discussion can be defined as follows:
Given:
[tex]\to \bold{g(n) = -3n^3 + 1 + n}\\\\\to \bold{h(n) = 3n - 2}\\\\[/tex]
To Find:
[tex]\to \bold{(g - h)(n)}[/tex]
Solution:
[tex]\to \bold{g(n) = -3n^3 + 1 + n}\\\\\to \bold{h(n) = 3n - 2}\\\\[/tex]
[tex]\to \bold{(g - h)(n)= g(n) - h(n)}[/tex]
[tex]\bold{= -3n^3+1+n- (3n-2)}\\\\\bold{= -3n^3+1+n- 3n+2}\\\\\bold{= -3n^3- 2n+3}\\\\\bold{= -3n^3- 2n+3}\\\\[/tex]
So, the final answer is "[tex]\bold{-3n^3-2n+3}[/tex]".
Learn more:
brainly.com/question/17426198